ICT Use at home for school-related tasks: what is the effect on a student's achievement? Empirical evidence from OECD PISA data. Issue 6 (1st November 2020) - Agasisti, Tommaso; Gil-Izquierdo, María; Han, Seong Won
ABSTRACT: In this paper, we have employed data from the OECD's Programme for International Student Assessment (PISA, 2012 edition) on the EU-15 countries in order to investigate the effect of using ICT at home on achievement. By employing Propensity Score Matching, we provide robust evidence that in most countries there is a negative association between using computers intensely for homework and achieving lower test scores across all subjects. Such negative effect affects the achievement of both low- and high-performing students and is robust to a specification that consider unobservable self-sorting of students across schools. Our findings suggest that a more cautious approach should be taken with regards to the wide-spread use of digital innovation as a means to support students' out-of-school work.